Legal Responsibilities of Companies to Consumers in the Perspective of the Consumer Protection Law - Debi Masri; Chairus Suriyat; Irna Herliza Rizki; Mela Novita Rizki (Outline Publisher, 2025)
This study examines the legal responsibility of companies towards consumers in the context of international consumer protection law. The main objective of this study is to analyze how the legal framework of consumer protection in different countries affects the level of corporate accountability. The results show that the successful implementation of consumer protection laws is highly dependent on the strength of national regulations and the strengthening of law enforcement, which in turn encourages more responsible corporate behavior. The study also finds that proactive judicial intervention and harmonization of international law, such as that carried out by the European Union, contribute to uniformity in the application of consumer protection. The development of e-commerce and digital risks also require changes in the legal system to protect consumers from threats such as privacy violations and online fraud. In addition, Corporate Social Responsibility (CSR) initiatives increasingly show that companies with strong CSR programs tend to exceed the minimum legal obligations to protect consumers. Overall, this study emphasizes the importance of continued legal reform and international cooperation in strengthening consumer protection and promoting corporate accountability globally.